Dampak Globalisasi Terhadap Eksistensi Pancasila Sebagai Staatsfundamentalnorm Bagi Bangsa Dan Negara Indonesia Dalam Pembentukan Hukum Nasional - Ridho Ansari Simanjuntak; Faisal Akbar; Sunarmi Sunarmi; M Yamin Lubis (Iuris Studia: Jurnal Kajian Hukum, 2021)
The influence of capitalism is characterized by the strong attraction of the free market and foreign investment. Facing this pressure, developing countries tend to be weak, even almost powerless. Pancasila as a philosophy in the life of the nation and state in Indonesia, is the ability of the values contained in Pancasila as a philosophy in facing every threat of globalization that affects all aspects of the life of the nation and state in Indonesia. Based on this, it is necessary to conduct research related to the impact of globalization on the existence of Pancasila as a staatsfundamental norm for the Indonesian nation and state in the formation of national law. The problem of this research is how is the influence of globalization in the economic field on the ideology adopted by a nation/state? How can Pancasila as a way of life for the Indonesian people become a filter from the influence of globalization in the economic field? How is Indonesian legal politics in maintaining the Pancasila legal system in the face of the influence of globalization in the economic field? The research method used in this research is normative legal research using a law approach, a conceptual approach and a case approach. The data sources of this research consist of primary data and secondary data. This research is descriptive analytical using qualitative data analysis. From the results of the study, it was found that globalization in the economic field has an impact on the ideology of the Indonesian nation and state, namely the inhibition of national economic development based on the concept of populist/kinship economy as stated in Article 33 of the 1945 Constitution of the Republic of Indonesia. Pancasila as a way of life for the Indonesian nation has not been able to become filter from the negative impacts arising from globalization in the economic field. Indonesian legal politics in maintaining the Pancasila legal system in facing the impact of globalization in the economic field requires the implementation of a people's economic system by providing people's economic protection.